The inflammatory response to Escherichia coli lipopolysaccharide is mitigated by in ovo delivery of carvacrol in broiler chicks - Mila M.Y. Meijer; Henry van den Brand; Marta Navarro; Eugeni Roura (Poultry Science)
The broiler chickens’ immune system fully develops a few weeks after hatching, leaving them susceptible to disease during the early post-hatching phase. This study investigated effects of in ovo delivery of carvacrol on the expression of immune-related genes following an Escherichia coli lipopolysaccharide (LPS) challenge at d7 post-hatch. The experiment was designed as a 2 × 2 factorial arrangement with two in ovo treatments (saline or carvacrol) and two LPS challenged groups (yes or no): (1) saline + no challenge (control), (2) saline + LPS, (3) carvacrol + no challenge, (4) carvacrol + LPS. Hatchability and performance parameters were determined before, and organ weights after the LPS challenge. Immune-related gene expression was assessed in the jejunum and spleen post-challenge. At d7, the carvacrol-treated group had lower FI (Δ11 g, P = 0.02) compared to the saline group. In the jejunum, a significant interaction (P = 0.003) was found between in ovo treatment and LPS challenge for IFN-γ expression, which was highest in the saline + LPS and carvacrol + no challenge groups. Carvacrol delivery resulted in lower IL-8 (P = 0.03) and IκB (P = 0.04) expression, regardless of LPS challenge. In the spleen, a significant interaction (P = 0.03) showed that carvacrol downregulated expression of pro-inflammatory IL-1β, observed in the saline + LPS group. For NF-κB and TLR4, LPS challenge did not affect saline-treated chickens, but lowered expression of these genes in carvacrol-treated chickens (P = 0.03 and 0.02, respectively). IFN-γ expression did not differ between in ovo delivery treatments after LPS challenge but was higher (P = 0.02) in the carvacrol-treated chickens than in the saline-treated chickens for the non-challenged groups. These findings indicate an anti-inflammatory effect of in ovo carvacrol delivery by inhibiting LPS-induced downregulation of NF-κB and mitigating IL-1β and TNF-α expression. Carvacrol stimulated IFN-γ expression, potentially modulating adaptive immune responses. In conclusion, in ovo carvacrol delivery could mitigate release of key inflammatory cytokines, while increasing IFN-γ.